Aléma da autossuficiência: O Brasil como protagonista no setor energético - Pedro Silva Barros; Giorgio Romano Schutte; Pinto Luiz Fernando Sanná (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The objective of this paper is to analyze the implications of the economic, strategic and political transformation of the Brazilian energetic scenario, considering their possible impact on the country's international insertion. For this purpose, a global energy outlook will be presented, which discusses the role of key players in the sector recent developments in oil prices and the participation of the different energy sources in global supply. Subsequently, the article will analyze the geopolitical importance of oil, nuclear and ethanol industries evolution in Brazil, highlighting trends and debates in each segment. The analysis concludes that the effort to avoid energy constraints to the development process, besides having achieved diversification of the energetic matrix and self-sufficiency, started off relevant institutional and technological progress in the various energy industries, which created the conditions that, currently, made the country emerge as a relevant net energy exporter.
Keywords: Q48; 330; Energy; Brazil; Oil; Ethanol; Nuclear; Energieversorgung; Energieprognose; Brasilien